Gerakan Sedekah Sampah Di Kelurahan Bujel Kota Kediri - Oktio Frenki Biantoro; Asep Rahmatullah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The problem of waste has become a crucial issue in the life of modern society, not only because of its impact on the environment, but also because of its relationship with people's health and quality of life. The rosok waste alms management training program in Bujel Village, Kediri City, is a form of community service innovation that aims to overcome the waste problem through a religion-based participatory approach. The method used in this research is qualitative with a descriptive approach, with data collection techniques through observation, interviews, and documentation. The results show that this program not only increases people's understanding of sorting and managing waste in an environmentally friendly manner, but also has social and economic impacts such as increasing musholla operational funds, empowering underprivileged residents, and reducing the volume of waste by 35% to landfills. Thus, this waste alms management model is expected to be replicated in various regions as an integrative solution in sustainable community-based waste management.